Desafios e Objetivos da Comissão de Ética Ambiental - Okamoto, Ana Cláudia; Piedade, André Luís Mattos; Maeoka, Kátia Midori Yabuke; Cocato, Anne Cristina de Faria; Ossune, Anny Kellen; Garbin, Artênio José Isper; Poi, Isabel Cristina Lui; Cintra, Luciano Tavares Ângelo; Poi, Wilson Roberto; Ávalos, Yara Regina Bianchine (ARCHIVES OF HEALTH INVESTIGATION, 2013)
Apresentação Ana Cláudia Okamoto André Luís Mattos Piedade Kátia Midori Yabuke Maeoka